Hospital Topics: The Hospital Consultant's Secretary - Gooch, J. H. (1972)
Analysis of work done by the secretaries attached to one medical unit in a general hospital showed that much was discretionary in character and entailed making decisions. Work in the unit was made easier and more efficient by this intelligent use of initiative by the secretaries. At present the pay given to medical secretaries in hospital is below a level that would be commensurate with their responsibility.